Proceedings of the National worshop sustainable and economically efficient utilization of natural resouces in mangrove ecosystem : (CRES & ACTMANG, 1999)
Many papers mention the irrational use of national resouces which led to the serious diterioration of mangrove ecosystem due to the lack of coordination between branches in management and inadequate policies, as well as point out the pressing problems need to be solved in the localities. Based on research result over many years, some papers estamate the economic and environmental impact of biodiversity mangrove restoration,...